Plan estratégico para mejorar la gestión turística post terremoto del 16 de abril del 2016 en el cantón Bolívar - Manabí - Basurto Mendoza, José Gabriel (2017)
The present research was developed with the purpose of improving the post-earthquake tourism management of April 16, 2016 in Bolívar through the proposal of a strategic plan which responds to current problems and trends in tourism. To comply with the proposed, a fourth phase methodology was established: the first consisted of a post-earthquake diagnosis, identifying the current situation in areas such as social, economic and environmental, identified several issues in the tourism sector as the collapse of several representative resources of the canton, a limited tourism planning is evidenced due to the non-existent interinstitutional work between the public, private and community sectors, the information was compiled based on interviews and surveys. The second phase focuses on determining the strategic positioning of the canton through the implementation of the SWOT Matrix, allowing to identify as one of the main weaknesses the lack of a strategic plan for local tourism management; the third phase focused on identifying strategies to manage the tourism activity in an appropriate manner and sustained in long-term tourism planning; and in the fourth phase the strategic plan was proposed with its mission, vision, values, corporate goals, strategic objectives, and mainly its 9 programs and 19 projects directed to the restructuring of the internal processes and improvement of tourist resources, besides of other aspects that must be done to improve local tourism management.